Misclassification of self‐reported smoking in adult survivors of childhood cancer. Issue 9 (1st June 2018) - Huang, I‐Chan; Klosky, James L.; Young, Chelsea M.; Murphy, Sharon E.; Krull, Kevin K.; Srivastava, DeoKumar; Hudson, Melissa M.; Robison, Leslie L.
Abstract: We investigated misclassification rates, sensitivity, and specificity of self‐reported cigarette smoking through serum cotinine concentration (liquid chromatography tandem mass spectrometry) among 287 adult survivors of childhood cancer. Overall, 2.5–6.7% and 19.7–36.9% of the self‐reported never and past smokers had cotinine levels indicative of active smoking. Sensitivity and specificity of self‐reported smoking were 57.5–67.1% and 96.6–99.2%. Misclassification was associated with younger age (OR = 3.2; 95% CI = 1.4–7.4), male (OR = 2.1; 95% CI = 1.1–4.0), and past (OR = 2.7; 95% CI = 1.3–5.8) or current (OR = 2.6; 95% CI = 1.0–6.6) marijuana use. After adjusting for tobacco‐related variables, current marijuana use remained a significant risk for misclassification. Clinicians/researchers should consider bio‐verification to measure smoking status among survivors.